Golf ball
Patent Information
- Application Number
- JP2023127130
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-03
- Publication Date
- 2025-02-14
AI Technical Summary
【0025】 本発明によれば、アプローチショットの初速が低く、コントロール性に優れ、アプローチショットの打球感が良好なボールを提供することができる。
Smart Images

Figure 2025022493000007 
Figure 2025022493000001 
Figure 2025022493000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a golf ball, and more particularly to a golf ball that stops easily on approach shots. [Background technology]
[0002] A golf ball generally comprises a spherical core and a cover. The spherical core is made of a rubber composition containing a base rubber and a co-crosslinking agent, and has a hardness distribution.
[0003] Patent Document 1 discloses a golf ball comprising a core and a cover, the core being formed from a rubber composition containing a base rubber, a co-crosslinking agent, a crosslinking initiator and a metal oxide, the co-crosslinking agent being methacrylic acid, the metal oxide being zinc oxide, the rubber composition containing an organic sulfur compound, the amount of the crosslinking initiator being 1.2 to 5 parts by mass per 100 parts by mass of the base rubber, and the initial velocity of the finished ball being 74.3 m / s or more.
[0004] Patent Document 2 discloses a solid golf ball comprising a core and a cover, the core being formed from a rubber composition containing a base rubber, a co-crosslinking agent, a crosslinking initiator, and a metal oxide, the base rubber being a mixture of polybutadiene and styrene-butadiene rubber, the styrene-butadiene rubber having a styrene bond amount of 35 mass% or less, and methacrylic acid being used as the co-crosslinking agent, the core having a deflection (CH) of 2.5 to 7.0 mm when subjected to an initial load of 98 N (10 kgf) and a final load of 1,275 N (130 kgf), and further having a ratio (VR) of 0.95 to 1.7 of the total volume of dimple spaces formed below a plane surrounded by the edges of the dimples to the volume of a virtual sphere assuming no dimples exist on the ball surface.
[0005] Patent Document 3 discloses a practice golf ball comprising a core and a cover, the core being formed from a rubber composition containing a base rubber, a co-crosslinking agent, a crosslinking initiator, and a metal oxide, the base rubber being a mixture of polybutadiene and styrene butadiene rubber and / or isoprene rubber, and the co-crosslinking agent being methacrylic acid, the core having a deflection CH of 2.5 to 7.0 mm when the core is loaded with an initial load of 98 N (10 kgf) to a final load of 1,275 N (130 kgf), the initial velocity of the ball being 70 m / s or less, and further the ratio (VR) of the total dimple space volume formed below a plane surrounded by the edges of the dimples to the volume of a virtual sphere assuming no dimples exist on the ball surface being 0.95 to 1.7.
[0006] Patent Document 4 describes a practice golf ball that is made up of a core and a cover, the core being made of a rubber composition containing a base rubber, a co-crosslinking agent, a crosslinking initiator, and a metal oxide. Methacrylic acid is used as the co-crosslinking agent, and zinc oxide is used as the metal oxide. In addition, in the hardness distribution of the core, the JIS-C hardness of the core surface is (A), the JIS-C hardness of a portion 2 mm inward from the core surface is (B), and the JIS-C hardness of a portion 5 mm inward from the core surface is (C). C), the JIS-C hardness of a portion 10 mm inward from the core surface is (D), the JIS-C hardness of a portion 15 mm inward from the core surface is (E), and the JIS-C hardness of the core center is (F). (A) is 65 to 77, (B) is 59 to 70, (C) is 61 to 74, (D) is 59 to 75, (E) is 61 to 70, and (F) is 57 to 67. In addition, the hardness relationship of (A)>(B)<(C)≧(D)>(E)>(F) is satisfied, and the value of (A)-(F) is within 1. 9 or less, (A) being the hardest of (A) through (F), the value of (A) - (C) is 0 to 8, the core specific gravity is 1.05 to 1.2, the cover resin component is primarily polyurethane, the cover thickness is 0.3 to 1.9 mm, and the cover material hardness is 30 to 48 Shore D hardness, and further, when the core and ball are subjected to an initial load of 98 N (10 kgf) and a final load of 1,275 N (130 kgf), The disclosed practice golf ball is characterized in that, when the deflection amounts of the core and ball are (CH) and (BH1), respectively, (CH) is 2.8 to 7.0 mm, and the value of (CH) / (BH1) is 0.95 to 1.1, and further, the ratio (VR) of the total volume of the dimple spaces formed below the plane surrounded by the edges of the dimples to the volume of a virtual sphere assuming no dimples exist on the ball surface is 0.95 to 1.7.
[0007] Patent Document 5 describes a practice golf ball comprising a core and a cover, the core being formed of a rubber composition containing a base rubber, a co-crosslinking agent, a crosslinking initiator, and a metal oxide, and using methacrylic acid as the co-crosslinking agent. In the hardness distribution of the core, when the JIS-C hardness of the core surface is (A), the JIS-C hardness of a portion 2 mm inward from the core surface is (B), the JIS-C hardness of a portion 5 mm inward from the core surface is (C), the JIS-C hardness of a portion 10 mm inward from the core surface is (D), the JIS-C hardness of a portion 15 mm inward from the core surface is (E), and the JIS-C hardness of the core center is (F), (A) is 70 to 88, (B) is 64 to 83, (C) is 66 to 85, (D) is 64 to 80, (E) is 61 to 75, and (F) is 58 to 72, and (A)>(B)<(C). The present invention discloses a practice golf ball which satisfies the hardness relationship of (A)≧(D)>(E)>(F), and the value of (A)-(F) is 19 or less, and of (A) to (F), (A) is formed to be the hardest, and the value of (A)-(C) is 1 to 8, the core specific gravity is 1.05 to 1.2, the resin component of the cover is mainly made of polyurethane, the cover thickness is 0.3 to 1.9 mm, and the cover material hardness is 30 to 57 in Shore D hardness, and further, when the core and the ball are subjected to an initial load of 98 N (10 kgf) to a final load of 1,275 N (130 kgf), the deflection of the core and the ball are (CH) and (BH1), respectively, and (CH) is 2.0 to 4.0 mm, and the value of (CH) / (BH1) is 0.95 to 1.1.
[0008] Patent Document 6 discloses a practice golf ball that comprises a core, a cover, and a transparent paint layer, the core being formed from a rubber composition containing a base rubber, a co-crosslinking agent, a crosslinking initiator, and a metal oxide, and that uses methacrylic acid as the co-crosslinking agent, and that the resin material that forms the cover has a breaking strength of 20 to 80 MPa, an elongation of 150 to 600%, and an initial velocity (BV) of the ball of 76 m / s or less.
[0009] Patent Document 7 discloses a practice golf ball comprising a core and a cover, the core being formed from a rubber composition containing a base rubber, a co-crosslinking agent, a crosslinking initiator and a metal oxide, wherein methacrylic acid is used as the co-crosslinking agent, and the practice golf ball is characterized in that when the core and the ball are subjected to an initial load of 98 N (10 kgf) to a final load of 1,275 N (130 kgf), the deflections of the core and the ball are (CH) and (BH1), respectively, and the value of (CH) / (BH1) is 0.95 to 1.1.
[0010] Patent Document 8 describes a ball that includes a core and a cover, and when loaded with an initial load of 98 N (10 kgf) to a final load of 1,275 N (130 kgf), the ball has a deflection BH in the range of 2.0 to 4.5 mm. The driver (W#1) is a Bridgestone Sports TourStage X-DRIVE701 (loft angle: 9°) that is attached to a hitting robot, and the ball is hit at a head speed (HS) of 52 m / s. The carry C is preset and calculated based on the following formula (1): C=A-33×BH (1) (However, 295≦A≦325) The present invention discloses a practice golf ball in which the amount of deflection BH of the ball is adjusted so as to satisfy the following:
[0011] Patent Document 9 describes a practice golf ball consisting of a core and a cover, in which the amount of deflection of the ball when it is initially measured and loaded with an initial load of 98N (10kgf) to a final load of 1,275N (130kgf) is taken as BH1 (mm) and the initial velocity of the ball is taken as BV1 (m / s), and the amount of deflection of the ball when it is loaded with an initial load of 98N (10kgf) to a final load of 1,275N (130kgf) after the ball has been left to stand for 350 days from the initial measurement is taken as BH2 (mm) and the initial velocity of the ball is BV1 (m / s), the difference between BH2-BH1 is within 0.2mm and the difference between BV2-BV1 is within 0.3m / s.
[0012] Patent Document 10 discloses a practice golf ball comprising a core and a cover, the core being formed from a rubber composition containing a base rubber, a co-crosslinking agent, a crosslinking initiator, and a metal oxide, the practice golf ball using methacrylic acid as the co-crosslinking agent, and characterized in that the resin material of the cover has a breaking strength of 20 to 80 MPa and an elongation of 150 to 600%.
[0013] Patent Document 11 discloses a practice golf ball that comprises a core and a cover, the core being formed from a rubber composition containing a base rubber and a co-crosslinking agent, in which methacrylic acid is used as the co-crosslinking agent, and the initial velocity of the ball is 76 m / s or less.
[0014] Patent Document 12 discloses a practice golf ball which comprises a core and a cover, the material hardness of the cover being 30 to 57 Shore D hardness, and further, where the initial velocity of the core is CV (m / s) and the initial velocity of the ball is BV1 (m / s), the value of CV-BV1 satisfies the following formula (1): (CV-BV1)=0.7×(cover thickness)-b (1) (However, 0.1≦b≦1.0)
[0015] Patent Document 13 discloses a golf ball for use at driving ranges obtained by vulcanizing a composition containing 100 parts by weight of base rubber, 3 to 35 parts by weight of low-resilience rubber, 20 to 30 parts by weight of methacrylic acid, and 20 to 50 parts by weight of a metal compound capable of forming a metal salt with methacrylic acid.
[0016] Patent Document 14 discloses a solid golf ball consisting of a core and a cover formed on the core, characterized in that the core is obtained from a rubber composition obtained by compounding 20 to 40 parts by weight of methacrylic acid and 20 to 40 parts by weight of zinc oxide with 100 parts by weight of a base rubber, generating basic zinc methacrylate as the main component in the rubber, and reacting this composition with 0.1 to 3.0 parts by weight of an organic peroxide and 0.1 to 3.0 parts by weight of an organic sulfur compound.
[0017] Patent Document 15 describes a multi-piece solid golf ball having a core, an intermediate layer, and a cover, in which the core is formed mainly from a base rubber and has a diameter of 32 mm or more, and each layer of the intermediate layer and the cover is formed from a resin material, and the Shore C hardness at the center of the core is Cc, the Shore C hardness at a position 2 mm from the center of the core is C2, the Shore C hardness at a position 4 mm from the center of the core is C4, the Shore C hardness at a position 6 mm from the center of the core is C6, the Shore C hardness at a position 8 mm from the center of the core is C8, the Shore C hardness at a position 10 mm from the center of the core is C10, and the Shore C hardness at a position 10 mm from the center of the core is C11. When the Shore C hardness at a position 12 mm from the center is C12, the Shore C hardness at a position 14 mm from the core center is C14, the Shore C hardness at a position 16 mm from the core center is C16, the Shore C hardness on the core surface is Cs, the Shore C hardness at a position 3 mm inside from the core surface is Cs-3, and the hardness at the intermediate position between the core surface and the core center is Cm, the values of C8-C6, C6-C4, C4-C2, and C2-Cc are all within 4.0, the values of C16-C14, C14-C12, C12-C10, and C10-C8 are all within 5.5, and the values satisfy the following formulas (1), (2), and (3): Cs-Cc≧22 (1) (Cs-Cm) / (C4-Cc)≧4.0 ···(2) Cs-Cs-3≦5.0 (3) and the surface hardness of a sphere obtained by covering the core with an intermediate layer (an intermediate layer-covered sphere) and the surface hardness of the ball satisfy the following formula: Ball surface hardness < Surface hardness of ball with intermediate layer (4) (However, the hardness of each layer mentioned above means the Shore C hardness value.) A multi-piece solid golf ball is disclosed which satisfies the following:
[0018] Patent Document 16 discloses a multi-piece solid golf ball having an intermediate layer interposed between a core and a cover, characterized in that the surface hardnesses of the core, a sphere surrounded by an intermediate layer (intermediate layer-coated sphere), and the ball satisfy the relationship of, in Shore D hardness, ball surface hardness≦surface hardness of intermediate layer-coated sphere≧surface hardness of core, the thickness of the intermediate layer and the thickness of the cover satisfy the relationship of, (intermediate layer thickness-cover thickness)≧0, and the core hardness distribution satisfies the relationships, in JIS-C hardness, of 22≦core surface hardness (Cs)-core center hardness (Cc), 5≧[hardness at a position 5 mm from the core center (C5)-core center hardness (Cc)]>0, [core surface hardness (Cs)-core center hardness (Cc)] / [hardness at a position midway between the core surface and center (Cm)-core center hardness (Cc)]≧4. [Prior art documents] [Patent documents]
[0019] [Patent Document 1] JP 2014-050696 A [Patent Document 2] JP 2014-069045 A [Patent Document 3] JP 2012-228470 A [Patent Document 4] JP 2012-228468 A [Patent Document 5] JP 2012-228465 A [Patent Document 6] JP 2012-228461 A [Patent Document 7] JP 2012-228458 A [Patent Document 8] JP 2012-228457 A [Patent Document 9] JP 2012-228456 A [Patent Document 10] JP 2012-228452 A [Patent Document 11] JP 2012-228448 A [Patent Document 12] JP 2012-228447 A [Patent Document 13] Japanese Patent Application Publication No. 60-92780 [Patent Document 14] Japanese Patent Application Publication No. 10-192446 [Patent Document 15] Patent Publication No. 2021-62036 [Patent Document 16] JP 2016-112308 A Summary of the Invention [Problem to be solved by the invention]
[0020] An approach shot is a shot in which a golf ball is brought closer to a cup from around the green, and control of the golf ball in the approach shot is important for making a good score in golf.
[0021] For advanced golfers, the variation in the impact point on approach shots is small, so the amount of spin is stable, but if the initial speed of the ball on an approach shot is fast, the ball tends to roll and is difficult to control. Furthermore, for average golfers, the variation in the impact point is large, so the amount of spin is not stable, making it difficult to stop the golf ball on an approach shot. In particular, if the ball is launched too fast on an approach shot, it may roll on the green and deviate significantly from the target.
[0022] The present invention has been made in consideration of the above circumstances, and has an object to provide a ball that has a low initial velocity on approach shots, is excellent in controllability, and provides a good hitting feel on approach shots by improving the core. [Means for solving the problem]
[0023] The golf ball of the present invention which has solved the above problems is a golf ball having a spherical core, one or more intermediate layers positioned outside the spherical core, and a cover positioned outside the intermediate layer, the spherical core is formed from a rubber composition containing a rubber component, a co-crosslinking agent, and a crosslinking initiator; the co-crosslinking agent comprises methacrylic acid and / or a metal salt thereof; The center hardness (Shore C hardness) of the spherical core, the hardness (Shore C hardness) at points 2.5 mm, 5 mm, 7.5 mm, 10 mm, 12.5 mm, and 15 mm from the center toward the surface of the spherical core, and the surface hardness (Shore C hardness) of the spherical core are respectively designated as H0, H 2.5 , H5, H 7.5 , H 10 , H 12.5 , H 15 , H S When this is set, the following relationship is satisfied: H0 <H 2.5 <H5<H 7.5 <H 10 <H 12.5 <H 15 <H S
[0024] The golf ball of the present invention, having a spherical core constructed as described above, can reduce the initial velocity of the ball on approach shots. A golf ball with a low initial velocity on approach shots has excellent controllability because it does not roll too quickly. In addition, the spherical core provides the golf ball with a good shot feeling on approach shots. Effect of the Invention
[0025] According to the present invention, it is possible to provide a ball that has a low initial velocity on approach shots, is excellent in controllability, and provides a good hitting feel on approach shots. [Brief description of the drawings]
[0026] [Figure 1] 1 is a partially cutaway cross-sectional view showing a golf ball according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0027] The golf ball of the present invention is a golf ball having a spherical core, one or more intermediate layers positioned outside the spherical core, and a cover positioned outside the intermediate layer, the spherical core is formed from a rubber composition containing a rubber component, a co-crosslinking agent, and a crosslinking initiator, The co-crosslinking agent comprises methacrylic acid and / or a metal salt thereof, The center hardness (Shore C hardness) of the spherical core, the hardness (Shore C hardness) at 2.5 mm, 5 mm, 7.5 mm, 10 mm, 12.5 mm, and 15 mm from the center toward the surface of the spherical core, and the surface hardness (Shore C hardness) of the spherical core are respectively designated as H0, H 2.5 , H5, H 7.5 , H 10 , H 12.5 , H 15 , H S When this is set, the following relationship is satisfied: H0 <H 2.5 <H5<H 7.5 <H 10 <H 12.5 <H 15 <H S
[0028] The center hardness (Shore C hardness) of the spherical core and the hardness (Shore C hardness) at points 2.5 mm, 5 mm, 7.5 mm, 10 mm, 12.5 mm, and 15 mm from the center of the spherical core toward the surface are measured by cutting the spherical core along a plane passing through the center of the spherical core and measuring the hardness at the center of the cut surface and at points at a specified distance from the center. The surface hardness of the spherical core is measured on the surface of the spherical core.
[0029] In a preferred embodiment of the present invention, (H 2.5 -H0), (H5-H 2.5 ), (H 7.5 -H5), (H 10 -H 7.5 ), (H 12.5 -H 10 ), (H 15 -H12.5 ), and (H S -H 15 ) are preferably 5 or less. 2.5 -H0), (H5-H 2.5 ), (H 7.5 -H5), (H 10 -H 7.5 ), (H 12.5 -H 10 ), (H 15 -H 12.5 ), and (H S -H 15 ) is 5 or less, deformation of the entire core becomes smooth, resulting in a good hitting feel for each club.
[0030] (H 2.5 -H0), (H5-H 2.5 ), (H 7.5 -H5), (H 10 -H 7.5 ), (H 12.5 -H 10 ), (H 15 -H 12.5 ), and (H S -H 15 ) are preferably 0 or more. 2.5 -H0), (H5-H 2.5 ), (H 7.5 -H5), (H 10 -H 7.5 ), (H 12.5 -H 10 ), (H 15 -H 12.5 ), and (H S -H 15 ) is 0 or more, the core will be hard on the outside and soft on the inside, resulting in good driver distance performance.
[0031] Hardness (H 2.5 ) and the hardness difference between the center of the spherical core (H 2.5 The hardness difference (H −H0) is preferably 5 or less, more preferably 4.5 or less, and even more preferably 4 or less, in Shore C hardness. 2.5The lower limit of the hardness difference (H −H0) is not particularly limited, but is preferably 0 or more, more preferably 1 or more, and even more preferably 1.5 or more in Shore C hardness. 2.5 −H0) within the above range reduces the amount of spin upon driver shots.
[0032] Hardness (H 7.5 The difference in hardness (H ) between the hardness at the point 5 mm from the center of the spherical core (H5) 7.5 The hardness difference (H -H5) is preferably 5 or less, more preferably 4.8 or less, and even more preferably 4.5 or less, in Shore C hardness, and is preferably 0 or more, more preferably 1 or more, and even more preferably 2 or more. 7.5 -H5) within the above range provides a good hitting feel upon driver shots.
[0033] Hardness (H 10 ) and the hardness (H 7.5 ) and hardness difference (H 10 -H 7.5 ) is preferably 5 or less, more preferably 4.8 or less, and even more preferably 4.5 or less, in Shore C hardness, and is preferably 0 or more, more preferably 1 or more, and even more preferably 2 or more. 10 -H 7.5 ) is within the above range, the hitting feel upon iron shots is good.
[0034] Hardness (H 15 ) and the hardness (H 12.5 ) and hardness difference (H 15 -H 12.5) is preferably 5 or less, more preferably 4 or less, and even more preferably 3 or less, and is preferably 0 or more, more preferably 0.3 or more, and even more preferably 0.5 or more, in Shore C hardness. 15 -H 12.5 ) is within the above range, the hitting feel upon iron shots is good.
[0035] Surface hardness H of spherical core S and the hardness (H 15 ) and hardness difference (H S -H 15 ) is preferably 5 or less, more preferably 4 or less, and even more preferably 3 or less, and is preferably 0 or more, more preferably 0.3 or more, and even more preferably 0.5 or more, in Shore C hardness. S -H 15 ) is within the above range, a good hitting feeling can be obtained when hitting with a putter.
[0036] Surface hardness of spherical core (H S ) and the central hardness (H S The hardness difference (H -H0) is preferably 20 or less, more preferably 19 or less, and even more preferably 18 or less, and is preferably 5 or more, more preferably 6 or more, and even more preferably 7 or more, in Shore C hardness. s -H0) within the above range results in good spin performance and a good shot feel on shots with short irons.
[0037] The surface hardness of the spherical core (H S The surface hardness (H) is not particularly limited, but is preferably 70 or more, more preferably 71 or more, and even more preferably 72 or more in Shore C hardness, and is preferably 80 or less, more preferably 79 or less, and even more preferably 78 or less. S) within the above range, a good shot feeling can be obtained when hitting with a putter.
[0038] The central hardness (H0) of the spherical core is not particularly limited, but is preferably 48 or more, more preferably 49 or more, and even more preferably 50 or more, and is preferably 60 or less, more preferably 59 or less, and even more preferably 58 or less, in Shore C hardness. If the central hardness (H0) of the spherical core is within the above range, a good shot feeling can be obtained when hitting a long shot.
[0039] The spherical core of the golf ball of the present invention is preferably formed from a rubber composition containing (a) a rubber component, (b) a co-crosslinking agent, and (c) a crosslinking initiator (hereinafter, sometimes referred to as the "core rubber composition").
[0040] As the (a) rubber component, natural rubber and / or synthetic rubber can be used, for example, polybutadiene rubber, natural rubber, butyl rubber, polyisoprene rubber, styrene polybutadiene rubber, ethylene-propylene-diene rubber (EPDM), etc. These may be used alone or in combination of two or more. Among these, high cis polybutadiene having cis-1,4-bonds of 40 mass% or more, preferably 80 mass% or more, more preferably 90 mass% or more, which is advantageous in processability, is particularly suitable.
[0041] The high-cis polybutadiene preferably has a 1,2-vinyl bond content of 2 mass% or less, more preferably 1.7 mass% or less, and further preferably 1.5 mass% or less. If the 1,2-vinyl bond content is 2 mass% or less, the rubber composition has good processability and is homogeneous.
[0042] The high-cis polybutadiene is preferably one synthesized using a rare earth element catalyst. In particular, the use of a neodymium-based catalyst using a neodymium compound, which is a lanthanum series rare earth element compound, is preferred because it can produce a polybutadiene rubber having a high content of 1,4-cis bonds and a low content of 1,2-vinyl bonds with excellent polymerization activity.
[0043] The high cis polybutadiene has a Mooney viscosity (ML 1+4 (100°C)) is preferably 30 or more, more preferably 32 or more, even more preferably 35 or more, and is preferably 140 or less, more preferably 120 or less, even more preferably 100 or less, and most preferably 80 or less. Note that the Mooney viscosity (ML 1+4 (100°C) is a value measured in accordance with JIS K6300 using an L rotor with a preheating time of 1 minute, rotor rotation time of 4 minutes, and at 100°C.
[0044] The high cis polybutadiene preferably has a molecular weight distribution Mw / Mn (Mw: weight average molecular weight, Mn: number average molecular weight) of 2.0 or more, more preferably 2.2 or more, even more preferably 2.4 or more, most preferably 2.6 or more, and preferably 6.0 or less, more preferably 5.0 or less, even more preferably 4.0 or less, and most preferably 3.4 or less. If the molecular weight distribution (Mw / Mn) of the high cis polybutadiene is 2.0 or more, the workability is improved, and if it is 6.0 or less, the processability is improved. The molecular weight distribution is measured by gel permeation chromatography (manufactured by Tosoh Corporation, "HLC-8120GPC") using a differential refractometer as a detector under the conditions of column: GMHHXL (manufactured by Tosoh Corporation), column temperature: 40°C, and mobile phase: tetrahydrofuran, and is calculated as a standard polystyrene equivalent value.
[0045] The core rubber composition preferably contains polybutadiene rubber and (butyl rubber and / or polyisoprene rubber) as rubber components. That is, the core rubber composition may contain polybutadiene rubber and butyl rubber as rubber components, polybutadiene rubber and polyisoprene rubber as rubber components, or polybutadiene rubber, butyl rubber and polyisoprene rubber as rubber components. By containing butyl rubber and / or polyisoprene rubber in addition to polybutadiene rubber, the rubber component can easily adjust the resilience performance of the golf ball, making it possible to achieve the desired resilience performance.
[0046] The content ratio of polybutadiene rubber to (butyl rubber and / or polyisoprene rubber) [polybutadiene rubber / (butyl rubber and / or polyisoprene rubber)] is preferably 30 / 70 or more by mass, more preferably 40 / 60 or more, even more preferably 50 / 50 or more, preferably 95 / 5 or less, more preferably 90 / 10 or less, and even more preferably 85 / 15 or less. If the content ratio of polybutadiene rubber to (butyl rubber and / or polyisoprene rubber) is within the above range, the uniformity of the rubber can be ensured and the quality is stable.
[0047] The core rubber composition used in the present invention contains (b) a co-crosslinking agent. The (b) co-crosslinking agent has the effect of crosslinking rubber molecules by graft polymerization with the rubber component. The core rubber composition used in the present invention contains (b) methacrylic acid and / or a metal salt thereof as the co-crosslinking agent. (b) By containing methacrylic acid and / or a metal salt thereof as a co-crosslinking agent, a gentle hardness gradient is easily achieved, resulting in good controllability during approach shots.
[0048] Examples of metal ions constituting the metal salt of methacrylic acid include monovalent metal ions such as sodium, potassium, and lithium, divalent metal ions such as magnesium, calcium, zinc, barium, and cadmium, trivalent metal ions such as aluminum, and other ions such as tin and zirconium. The above metal components can be used alone or as a mixture of two or more kinds.
[0049] In the present invention, it is preferable to use methacrylic acid as the (b) co-crosslinking agent.
[0050] The content of the (b) co-crosslinking agent is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, even more preferably 20 parts by mass or more, and preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less, per 100 parts by mass of the (a) rubber component. If the content of the (b) co-crosslinking agent is 10 parts by mass or more, the core formed has an appropriate hardness and the durability of the golf ball is improved. On the other hand, if the content of the (b) co-crosslinking agent is 50 parts by mass or less, the core formed does not become too hard.
[0051] The (b) co-crosslinking agent may contain, in addition to methacrylic acid and / or a metal salt thereof, an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) and / or a metal salt thereof.
[0052] Examples of the α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) include acrylic acid, fumaric acid, maleic acid, and crotonic acid.
[0053] Examples of metals constituting metal salts of α,β-unsaturated carboxylic acids having 3 to 8 carbon atoms (excluding methacrylic acid) include monovalent metal ions such as sodium, potassium, and lithium; divalent metal ions such as magnesium, calcium, zinc, barium, and cadmium; trivalent metal ions such as aluminum; and other ions such as tin and zirconium. The metal components can be used alone or as a mixture of two or more kinds. Among these, divalent metals such as magnesium, calcium, zinc, barium, and cadmium are preferred as the metal components. This is because the use of divalent metal salts of α,β-unsaturated carboxylic acids having 3 to 8 carbon atoms facilitates the formation of metal crosslinks between rubber molecules.
[0054] When the (b) co-crosslinking agent contains, in addition to methacrylic acid and / or its metal salt, an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms (excluding methacrylic acid) and / or its metal salt, the content of methacrylic acid and / or its metal salt in the (b) co-crosslinking agent component is preferably 50% by mass or more, more preferably 60% by mass or more, even more preferably 70% by mass or more, preferably 99% by mass or less, more preferably 98% by mass or less, and even more preferably 97% by mass or less. If the content of methacrylic acid and / or its metal salt is within the above range, the reactivity in the rubber becomes uniform and the quality is stable. It is also preferable to contain only methacrylic acid and / or its metal salt as the co-crosslinking agent, and more preferably to contain only methacrylic acid.
[0055] The (c) crosslinking initiator is blended to crosslink the (a) rubber component. As the (c) crosslinking initiator, an organic peroxide is suitable. Specific examples of the organic peroxide include dicumyl peroxide, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethyl-2,5-di(t-butylperoxy)hexane, and di-t-butyl peroxide. These organic peroxides may be used alone or in combination of two or more. Among these, dicumyl peroxide is preferably used.
[0056] The content of the (c) crosslinking initiator is preferably 0.2 parts by mass or more, more preferably 0.4 parts by mass or more, and even more preferably 0.6 parts by mass or more, and is preferably 5.0 parts by mass or less, more preferably 2.5 parts by mass or less, and even more preferably 1.0 part by mass or less, per 100 parts by mass of the (a) rubber component. If the content of the (c) crosslinking initiator is within the above range, the hardness of the formed core becomes appropriate, and the durability of the golf ball becomes good.
[0057] The rubber composition preferably further contains a metal compound (d). The metal compound (d) can be used, for example, to neutralize the co-crosslinking agent (b) in the rubber composition or to adjust the mass of the rubber composition.
[0058] Examples of the (d) metal compound include metal hydroxides such as magnesium hydroxide, zinc hydroxide, calcium hydroxide, sodium hydroxide, lithium hydroxide, potassium hydroxide, and copper hydroxide; metal oxides such as magnesium oxide, calcium oxide, zinc oxide, and copper oxide; and metal carbonates such as magnesium carbonate, zinc carbonate, calcium carbonate, sodium carbonate, lithium carbonate, and potassium carbonate. The (d) metal compound is preferably a divalent metal compound, and more preferably a zinc compound. This is because the divalent metal compound reacts with an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms to form a metal bridge. Furthermore, by using a zinc compound, a golf ball with good durability can be obtained. These (d) metal compounds may be used alone or in combination of two or more kinds.
[0059] The rubber composition may further contain (e) an organic sulfur compound. The (e) organic sulfur compound is not particularly limited as long as it is an organic compound having a sulfur atom in the molecule, and examples thereof include organic compounds having a thiol group (-SH) or a polysulfide bond having 2 to 4 sulfur atoms (-SS-, -SSS-, or -SSSS-), or metal salts thereof (-SM, -SMS-, etc., where M is a metal atom). Examples of the (e) organic sulfur compound include compounds belonging to thiophenols, thionaphthols, polysulfides, thiurams, thiocarboxylic acids, dithiocarboxylic acids, sulfenamides, dithiocarbamates, or thiazoles.
[0060] Examples of the thiophenols include thiophenol; thiophenols substituted with a fluoro group, such as 4-fluorothiophenol, 2,4-difluorothiophenol, 2,5-difluorothiophenol, 2,6-difluorothiophenol, 2,4,5-trifluorothiophenol, 2,4,5,6-tetrafluorothiophenol, and pentafluorothiophenol; and chlorothiophenol, such as 2-chlorothiophenol, 4-chlorothiophenol, 2,4-dichlorothiophenol, 2,5-dichlorothiophenol, 2,6-dichlorothiophenol, 2,4,5-trichlorothiophenol, 2,4,5,6-tetrachlorothiophenol, and pentachlorothiophenol. thiophenols substituted with a bromo group, such as 4-bromothiophenol, 2,4-dibromothiophenol, 2,5-dibromothiophenol, 2,6-dibromothiophenol, 2,4,5-tribromothiophenol, 2,4,5,6-tetrabromothiophenol, and pentabromothiophenol; thiophenols substituted with an iodo group, such as 4-iodothiophenol, 2,4-diiodothiophenol, 2,5-diiodothiophenol, 2,6-diiodothiophenol, 2,4,5-triiodothiophenol, 2,4,5,6-tetraiodothiophenol, and pentaiodothiophenol; or metal salts thereof.
[0061] Examples of the thionaphthols (naphthalene thiols) include 2-thionaphthol, 1-thionaphthol, 1-chloro-2-thionaphthol, 2-chloro-1-thionaphthol, 1-bromo-2-thionaphthol, 2-bromo-1-thionaphthol, 1-fluoro-2-thionaphthol, 2-fluoro-1-thionaphthol, 1-cyano-2-thionaphthol, 2-cyano-1-thionaphthol, 1-acetyl-2-thionaphthol, 2-acetyl-1-thionaphthol, and metal salts thereof.
[0062] The polysulfides are organic sulfur compounds having polysulfide bonds, and examples of the polysulfides include disulfides, trisulfides, and tetrasulfides. As the polysulfides, diphenyl polysulfides are preferred.
[0063] Diphenyl polysulfides include, in addition to diphenyl disulfide, bis(4-fluorophenyl) disulfide, bis(2,5-difluorophenyl) disulfide, bis(2,6-difluorophenyl) disulfide, bis(2,4,5-trifluorophenyl) disulfide, bis(2,4,5,6-tetrafluorophenyl) disulfide, bis(pentafluorophenyl) disulfide, bis(4-chlorophenyl) disulfide, Bis(2,5-dichlorophenyl) disulfide, bis(2,6-dichlorophenyl) disulfide, bis(2,4,5-trichlorophenyl) disulfide, bis(2,4,5,6-tetrachlorophenyl) disulfide, bis(pentachlorophenyl) disulfide, bis(4-bromophenyl) disulfide, bis(2,5-dibromophenyl) disulfide, bis(2,6-dibromophenyl) disulfide, bis(2,4,5-tribromophenyl) disulfide phenyl) disulfide, bis(2,4,5,6-tetrabromophenyl) disulfide, bis(pentabromophenyl) disulfide, bis(4-iodophenyl) disulfide, bis(2,5-diiodophenyl) disulfide, bis(2,6-diiodophenyl) disulfide, bis(2,4,5-triiodophenyl) disulfide, bis(2,4,5,6-tetraiodophenyl) disulfide, bis(pentaiodophenyl) disulfide diphenyl disulfides substituted with halogen groups such as bis(4-methylphenyl) disulfide, bis(2,4,5-trimethylphenyl) disulfide, bis(pentamethylphenyl) disulfide, bis(4-t-butylphenyl) disulfide, bis(2,4,5-tri-t-butylphenyl) disulfide, bis(penta-t-butylphenyl) disulfide, and the like.
[0064] Examples of thiurams include thiuram monosulfides such as tetramethylthiuram monosulfide, thiuram disulfides such as tetramethylthiuram disulfide, tetraethylthiuram disulfide, and tetrabutylthiuram disulfide, and thiuram tetrasulfides such as dipentamethylenethiuram tetrasulfide. Examples of thiocarboxylic acids include naphthalene thiocarboxylic acid. Examples of dithiocarboxylic acids include naphthalene dithiocarboxylic acid. Examples of sulfenamides include N-cyclohexyl-2-benzothiazole sulfenamide, N-oxydiethylene-2-benzothiazole sulfenamide, and Nt-butyl-2-benzothiazole sulfenamide.
[0065] The (e) organic sulfur compounds can be used alone or in combination of two or more.
[0066] The content of the (e) organic sulfur compound is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.2 parts by mass or more, and is preferably 5.0 parts by mass or less, more preferably 3.0 parts by mass or less, and even more preferably 2.0 parts by mass or less, based on 100 parts by mass of the (a) rubber component. If the content of the (e) organic sulfur compound is within the above range, the processability is good and the rubber composition becomes homogeneous.
[0067] The rubber composition may further contain (f) a carboxylic acid and / or a metal salt thereof. As the (f) carboxylic acid and / or a metal salt thereof, a carboxylic acid having 1 to 30 carbon atoms and / or a salt thereof is preferable. As the carboxylic acid, either an aliphatic carboxylic acid (saturated fatty acid, unsaturated fatty acid) or an aromatic carboxylic acid (benzoic acid, etc.) can be used. The compounding amount of the (f) carboxylic acid and / or a metal salt thereof is preferably 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the rubber component.
[0068] The rubber composition may contain additives such as a filler for adjusting the mass, an antioxidant, a peptizer, and a softener, as required.
[0069] The filler used in the rubber composition is mainly blended as a mass adjuster for adjusting the mass of the golf ball obtained as the final product, and may be blended as necessary. Examples of the filler include inorganic fillers such as zinc oxide, barium sulfate, calcium carbonate, magnesium oxide, tungsten powder, and molybdenum powder. The content of the filler is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 2 parts by mass or more, and is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less, relative to 100 parts by mass of the rubber component. If the content of the filler is 0.5 parts by mass or more, mass adjustment becomes easy, and if it is 30 parts by mass or less, the weight fraction of the rubber component increases, and durability tends to improve.
[0070] The content of the antioxidant is preferably 0.1 part by mass or more and 1 part by mass or less per 100 parts by mass of the (a) rubber component, and the content of the peptizing agent is preferably 0.1 part by mass or more and 5 parts by mass or less per 100 parts by mass of the (a) rubber component.
[0071] The rubber composition is obtained by kneading (a) a rubber component, (b) a co-crosslinking agent, (c) a crosslinking initiator, and other components that are mixed as necessary. The kneading method is not particularly limited, and may be performed using a known kneading machine such as a kneading roll, a Banbury mixer, or a kneader.
[0072] The spherical core can be molded, for example, by hot pressing the rubber composition for the core. The hot press molding conditions for the rubber composition for the core may be appropriately set depending on the rubber composition, but it is usually preferable to heat the rubber composition at 130°C to 200°C for 10 to 60 minutes, or to heat the rubber composition at 130°C to 150°C for 20 to 40 minutes, and then heat the rubber composition at 160°C to 180°C for 5 to 15 minutes in two stages.
[0073] The spherical core may have either a single-layer structure or a multi-layer structure, but is preferably of a single-layer structure.
[0074] The diameter of the spherical core is preferably 34.8 mm or more, more preferably 36.8 mm or more, even more preferably 38.0 mm or more, and is preferably 42.2 mm or less, more preferably 41.8 mm or less, even more preferably 41.2 mm or less, and most preferably 40.8 mm or less. If the diameter of the spherical core is 34.8 mm or more, the thickness of the cover is not too thick, and the hitting feeling is better. On the other hand, if the diameter of the spherical core is 42.2 mm or less, the cover is not too thin, and the function of the cover is more fully exhibited.
[0075] When the diameter of the spherical core is 34.8 mm to 42.2 mm, the amount of compressive deformation (the amount of shrinkage of the spherical core in the compressive direction) from when an initial load of 98 N is applied to when a final load of 1275 N is applied is preferably 2.0 mm or more, more preferably 2.5 mm or more, even more preferably 3.0 mm or more, and preferably 5.0 mm or less, more preferably 4.5 mm or less, even more preferably 4.0 mm or less. If the amount of compressive deformation is 2.0 mm or more, the hitting feeling on driver shots will be better, and if it is 5.0 mm or less, the durability will be better.
[0076] The golf ball of the present invention has a spherical core, one or more intermediate layers positioned outside the spherical core, and a cover positioned outside the intermediate layers. The cover is preferably a single layer. The outermost cover may be referred to as the outermost cover layer. The single layer cover corresponds to the outermost cover layer.
[0077] The structure of the golf ball of the present invention is not particularly limited, so long as it has a spherical core, one or more intermediate layers positioned outside the spherical core, and a cover positioned outside the intermediate layer.
[0078] Fig. 1 is a partially cutaway cross-sectional view illustrating an example of a golf ball of the present invention. The golf ball 2 shown in Fig. 1 has a spherical core 4, an intermediate layer 6 that encases the spherical core 4, and an outermost cover layer 8 located on the outside of the intermediate layer 6. The golf ball 2 has a plurality of dimples 10 on its surface. The portion of the surface of the golf ball 2 other than the dimples 10 is a land 12. The golf ball 2 has a paint layer and a mark layer on the outside of the outermost cover layer 8, but these layers are omitted from the illustration.
[0079] Examples of the golf ball of the present invention include a three-piece golf ball consisting of a spherical core, a single-layer intermediate layer arranged to cover the spherical core, and a single-layer cover that covers the intermediate layer; a multi-piece golf ball (including a three-piece golf ball) having a spherical core, one or more intermediate layers arranged to cover the spherical core, and a single-layer cover arranged to cover the intermediate layer. The present invention can be suitably used for golf balls of any of the above structures. The intermediate layer may be called an outer core layer or an inner cover layer depending on the structure of the golf ball.
[0080] (Cover composition, intermediate layer composition) The intermediate layer is preferably formed from an intermediate layer composition containing a resin component.The cover is preferably formed from a cover composition containing a resin component.
[0081] Examples of resin components used in the resin composition that forms the cover and intermediate layer include ionomer resins, urethane resins (thermoplastic polyurethane elastomers, thermosetting polyurethane elastomers), thermoplastic styrene elastomers, thermoplastic polyamide elastomers, and thermoplastic polyester elastomers.
[0082] Examples of the ionomer resin include a binary ionomer resin in which at least a portion of the carboxyl groups in a binary copolymer of an olefin and an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms are neutralized with a metal ion; a ternary ionomer resin in which at least a portion of the carboxyl groups in a ternary copolymer of an olefin, an α,β-unsaturated carboxylic acid having 3 to 8 carbon atoms, and an α,β-unsaturated carboxylic acid ester are neutralized with a metal ion; and a mixture thereof.
[0083] Examples of the binary ionomer resin include Himilan (registered trademark) 1555 (Na), 1557 (Zn), 1605 (Na), 1706 (Zn), 1707 (Na), AM7311 (Mg), AM7329 (Zn), and AM7337 (manufactured by Mitsui Dow Polychemicals); Surlyn (registered trademark) 8945 (Na), 9945 (Zn), 8140 (Na), 8150 (Na), 9120 (Zn), 9150 (Zn), 6910 (Mg), 6120 (Mg), 7930 (Li), 7940 (Li), and AD8546 (Li) (manufactured by DuPont); and Iotek (registered trademark) 8000 (Na), 8030 (Na), 7010 (Zn), and 7030 (Zn) (manufactured by ExxonMobil Chemicals).
[0084] Examples of the ternary ionomer resin include Himilan AM7327(Zn), 1855(Zn), 1856(Na), and AM7331(Na) (manufactured by Mitsui Dow Polychemicals); Surlyn 6320(Mg), 8120(Na), 8320(Na), 9320(Zn), 9320W(Zn), HPF1000(Mg), and HPF2000(Mg) (manufactured by DuPont); and Iotec 7510(Zn), 7520(Zn) (manufactured by ExxonMobil Chemicals). Note that Na, Zn, Li, Mg, and the like written in parentheses after the trade names of the ionomer resins indicate the metal species of these neutralizing metal ions.
[0085] The thermoplastic polyurethane elastomer has a urethane bond in the molecule. The urethane bond can be formed by the reaction of a polyol with a polyisocyanate. The polyol, which is the raw material for the urethane bond, has a plurality of hydroxyl groups, and a low molecular weight polyol and a high molecular weight polyol can be used.
[0086] Specific examples of the thermoplastic polyurethane elastomer include Elastollan (registered trademark) NY80A, NY84A, NY88A, NY95A, ET885, and ET890 (manufactured by BASF Japan Ltd.).
[0087] As the thermoplastic styrene-based elastomer, a thermoplastic elastomer containing a styrene block can be preferably used. The styrene block-containing thermoplastic elastomer has a polystyrene block as a hard segment and a soft segment.
[0088] The styrene block-containing thermoplastic elastomer includes styrene-butadiene-styrene block copolymer (SBS), styrene-isoprene-styrene block copolymer (SIS), styrene-isoprene-butadiene-styrene block copolymer (SIBS), hydrogenated SBS, hydrogenated SIS, and hydrogenated SIBS. Hydrogenated SBS includes styrene-ethylene-butylene-styrene block copolymer (SEBS). Hydrogenated SIS includes styrene-ethylene-propylene-styrene block copolymer (SEPS). Hydrogenated SIBS includes styrene-ethylene-ethylene-propylene-styrene block copolymer (SEEPS).
[0089] Examples of the thermoplastic styrene-based elastomer include TEFABLOC T3221C, T3339C, SJ4400N, SJ5400N, SJ6400N, SJ7400N, SJ8400N, SJ9400N, and SR04 (manufactured by Mitsubishi Chemical Corporation).
[0090] The cover composition constituting the cover preferably contains polyurethane and / or ionomer resin as a resin component, and more preferably contains polyurethane. When the cover contains polyurethane as a resin component, the outermost cover layer tends to bite into the club face more strongly on approach shots, which tends to increase the amount of spin.
[0091] When the cover composition contains polyurethane as a resin component, the content of polyurethane in the resin component is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. The cover composition may contain only polyurethane (preferably a thermoplastic polyurethane elastomer) as a resin component.
[0092] When the cover composition contains an ionomer resin as a resin component, the content of the ionomer resin in the resin component is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more. When the ionomer resin is contained, it is also preferable to use a thermoplastic styrene elastomer in combination.
[0093] The intermediate layer composition preferably contains an ionomer resin as a resin component. When the ionomer resin is contained, it is also preferable to use a thermoplastic styrene elastomer in combination. The content of the ionomer resin in the base resin of the intermediate layer composition is preferably 50% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more.
[0094] The cover composition and intermediate layer composition may contain, in addition to the resin components described above, pigment components such as white pigments (e.g., titanium oxide), blue pigments, and red pigments, weight adjusters such as zinc oxide, calcium carbonate, and barium sulfate, dispersants, antioxidants, ultraviolet absorbers, light stabilizers, fluorescent materials, or fluorescent brighteners.
[0095] The content of the white pigment (e.g., titanium oxide) is preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, and preferably 10 parts by mass or less, more preferably 8 parts by mass or less, based on 100 parts by mass of the base resin constituting the outermost cover. By making the content of the white pigment 0.5 parts by mass or more, it is possible to impart hiding properties to the cover. In addition, if the content of the white pigment is 10 parts by mass or less, the durability of the obtained cover is good.
[0096] The method for forming the intermediate layer is not particularly limited, but examples include a method in which the intermediate layer composition is first molded into a hemispherical half shell, two of which are used to encase a spherical core and then pressure molded, or a method in which the intermediate layer composition is directly injection molded onto the spherical core to encase the sphere.
[0097] Methods for molding the cover include, for example, a method in which a hollow shell is molded from the cover composition, and a sphere (a sphere with a spherical core or an intermediate layer) is coated with the multiple shells and compression molded (preferably, a method in which a hollow half shell is molded from the cover composition, and the sphere is coated with two half shells and compression molded), or a method in which the cover composition is directly injection molded onto the sphere.
[0098] The golf ball body with the molded cover is removed from the mold, and is preferably subjected to surface treatment such as deburring, cleaning, and sandblasting, as necessary.
[0099] The material hardness Hm of the intermediate layer composition constituting the intermediate layer is preferably 50 or more, more preferably 53 or more, and even more preferably 55 or more, and is preferably 75 or less, more preferably 73 or less, and even more preferably 71 or less, in Shore D hardness. If the material hardness Hm is 50 or more, the flight distance is improved due to the low spin rate on driver shots, and if it is 75 or less, the hitting feel on driver shots is improved. When a plurality of intermediate layers are provided, the material hardness Hm is the material hardness of the intermediate layer composition constituting the outermost intermediate layer.
[0100] The thickness Tm of the intermediate layer is preferably 0.8 mm or more, more preferably 0.9 mm or more, and even more preferably 1.0 mm or more, and is preferably 3.0 mm or less, more preferably 2.6 mm or less, and even more preferably 2.2 mm or less. If the thickness Tm is 0.8 mm or more, durability is good, and if it is 3.0 mm or less, a good hitting feeling is obtained at the time of a driver shot. In addition, when there are multiple intermediate layers, the total thickness of all the intermediate layers is defined as the thickness Tm of the intermediate layer.
[0101] The material hardness Hc of the cover composition constituting the cover is preferably 20 or more, more preferably 22 or more, and even more preferably 24 or more, and is preferably 40 or less, more preferably 38 or less, and even more preferably 36 or less. If the material hardness Hc is 20 or more, the amount of spin on driver shots will not be too large, resulting in good distance performance, and if it is 40 or less, the spin performance on approach shots will be even better.
[0102] The cover has a thickness Tc of preferably 0.4 mm or more, more preferably 0.5 mm or more, and even more preferably 0.6 mm or more, and is preferably 1.0 mm or less, more preferably 0.9 mm or less, and even more preferably 0.8 mm or less. If the thickness Tc is 0.4 mm or more, the spin performance on approach shots will be further improved, and if it is 1.0 mm or less, the spin amount on driver shots will not be too large, and the flight distance performance will be good.
[0103] The material hardness Hm of the intermediate layer is preferably greater than the material hardness Hc of the cover. The hardness difference (Hm-Hc) between the material hardness Hm of the intermediate layer and the material hardness Hc of the cover is preferably 20 or more, more preferably 22 or more, even more preferably 24 or more, and is preferably 40 or less, more preferably 39 or less, and even more preferably 38 or less, in Shore D hardness. If the hardness difference (Hm-Hc) is within the above range, the hitting feel at the time of a driver shot is improved.
[0104] If desired, a coating film or mark can be formed. The thickness of the coating film is not particularly limited, but is preferably 5 μm or more, more preferably 6 μm or more, even more preferably 7 μm or more, preferably 50 μm or less, more preferably 40 μm or less, and even more preferably 30 μm or less. If the thickness is 5 μm or more, the coating film is less likely to wear away even with continuous use, and if the thickness is 50 μm or less, the effect of the dimples can be fully obtained. Note that the coating film is very thin, so it does not impair the effect of the present invention.
[0105] The diameter of the golf ball of the present invention is preferably 40 mm to 45 mm. From the viewpoint of satisfying the standards of the United States Golf Association (USGA), the diameter is particularly preferably 42.67 mm or more. From the viewpoint of suppressing air resistance, the diameter is more preferably 44 mm or less, and particularly preferably 42.80 mm or less. The mass of the golf ball of the present invention is preferably 40 g or more and 50 g or less. From the viewpoint of obtaining a large inertia, the mass is more preferably 44 g or more, and particularly preferably 45.00 g or more. From the viewpoint of satisfying the standards of the USGA, the mass is particularly preferably 45.93 g or less.
[0106] In the golf ball of the present invention, when the diameter is 40 mm to 45 mm, the compressive deformation amount (the amount of contraction of the golf ball in the compressive direction) when a final load of 1275 N is applied from an initial load of 98 N is preferably 2.0 mm or more, more preferably 2.2 mm or more, even more preferably 2.4 mm or more, and preferably 3.5 mm or less, more preferably 3.3 mm or less, even more preferably 3.1 mm or less, and particularly preferably 2.8 mm or less. A golf ball with the compressive deformation amount of 2.0 mm or more is not too hard and has a good hitting feel on driver shots. On the other hand, by making the compressive deformation amount 3.5 mm or less, durability is improved. EXAMPLES
[0107] The present invention will be described in detail below with reference to examples. However, the present invention is not limited to the following examples, and all modifications and embodiments that do not deviate from the spirit of the present invention are included within the scope of the present invention.
[0108] [Evaluation method] (1) Compressive deformation amount (mm) A Yamada compression tester "SCH" was used to measure the amount of compressive deformation. In this tester, a golf ball or core is placed on a metal hard plate. A metal cylinder is gradually lowered towards the golf ball or core. The golf ball or core is deformed when sandwiched between the bottom of the cylinder and the hard plate. The travel distance of the cylinder was measured from when an initial load of 98N was applied to the golf ball or core until a final load of 1275N was applied. The amount of compressive deformation (mm) is this travel distance. The travel speed of the cylinder until the initial load was applied was 0.83mm / s. The travel speed of the cylinder from when the initial load was applied to when the final load was applied was 1.67mm / s.
[0109] (2) Material (slab) hardness (Shore D hardness) A sheet with a thickness of about 2 mm was prepared by injection molding using the intermediate layer composition or the cover composition, and stored at 23° C. for two weeks. The hardness was measured using an automatic hardness tester (Digitest II, manufactured by H. Burleith Co.) in a state where three or more sheets were stacked so as not to be affected by the measurement substrate, etc. The detector used was "Shore D."
[0110] (3) Core hardness distribution (Shore C hardness) An automatic hardness tester (H. Burleith, Digitest II) with a Shore C detector was used to measure the Shore C hardness on the surface of the spherical core, which was taken as the spherical core surface hardness. The spherical core was cut into a hemisphere along a plane passing through the center of the spherical core, and the hardness was measured at the center of the cut surface and at a specified distance in the radial direction from the center. Each hardness was calculated by measuring the hardness at four points and averaging these values.
[0111] (4) Ball speed (m / s), spin rate (rpm), and rolling distance (m) of approach (AP) shots A wedge "RTX3 BLD (loft angle 58°)" manufactured by Cleveland Golf was attached to a Golf Laboratory swing machine. The impact point was set at the face center. The golf ball was hit with a head speed of 16 m / sec, and the ball speed (m / s), backspin amount (rpm), and rolling distance (m) (distance from the landing point to the stopping point) immediately after impact were measured. The ball speed and backspin amount were measured by taking continuous photographs of the golf ball immediately after it was hit. Each golf ball was measured 12 times, and the average of the data obtained was used as the measurement value for that golf ball.
[0112] (5) Impact feel of approach shots based on actual hit tests Twenty golfers used a Cleveland Golf Company RTX3 BLD (loft angle 58°) wedge to hit approach shots 20 yards away and rated the feel of the ball on a three-point scale: hard, normal, or soft. Judgment criteria ◎: 16 or more golfers rated the shot feeling as soft Good: 12 or more golfers and 15 or less golfers rated the shot feeling as soft △: 8 or more golfers and 11 or less golfers rated the shot feeling as soft ×: Seven or fewer golfers rated the shot feeling as soft
[0113] [Manufacturing of golf balls] (1) Preparation of Core Composition The raw materials were kneaded with a kneading roll so as to obtain the composition shown in Table 1, thereby obtaining a core composition.
[0114] [Table 1]
[0115] The materials used in Table 1 are as follows: Polybutadiene: JSR "BR-730" Butyl rubber: Japan Butyl "Butyl 268" Isoprene rubber: "IR-2200" manufactured by Nippon Zeon Co., Ltd. Methacrylic acid: Mitsubishi Gas Chemical Company, Inc. Zinc acrylate: Nisshoku Techno Fine Chemical Co., Ltd., "ZN-DA90S" Zinc oxide: "Ginrei R" manufactured by Toho Zinc Co., Ltd. Barium sulfate: Sakai Chemical Industry Co., Ltd., "Barium Sulfate BD" Benzoic acid: Tokyo Chemical Industry Co., Ltd. (purity 98% or more) Bis(pentabromophenyl) disulfide: Kawaguchi Chemical Industry Co., Ltd. Diphenyl disulfide: Sumitomo Seika Chemicals Dicumyl peroxide: NOF Corporation, "Percumyl (registered trademark) D"
[0116] (2) Preparation of intermediate layer composition The raw materials were extruded using a twin-screw kneading extruder so as to obtain the composition shown in Table 2, to prepare pellets of an intermediate layer composition.
[0117] [Table 2] Surlyn® 8150: Sodium ion neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by DuPont Himilan (registered trademark) 1605: Manufactured by Mitsui Dow Polychemicals, sodium ion neutralized ethylene-methacrylic acid copolymer ionomer resin Himilan (registered trademark) AM7329: Sodium ion neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by Mitsui Dow Polychemicals Himilan (registered trademark) 1555: Sodium ion-neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by Mitsui Dow Polychemicals Himilan (registered trademark) 1557: Zinc ion neutralized ethylene-methacrylic acid copolymer ionomer resin manufactured by Mitsui Dow Polychemicals Tefablock T3221C: Thermoplastic styrene elastomer manufactured by Mitsubishi Chemical Corporation Titanium dioxide: Ishihara Sangyo Kaisha, A-220
[0118] (3) Preparation of cover composition The raw materials were extruded by a twin-screw kneading extruder so as to have the composition shown in Tables 2 and 3, to prepare pellets of a cover composition.
[0119] [Table 3] Elastollan (registered trademark) NY80A: BASF Japan, thermoplastic polyurethane elastomer Elastollan (registered trademark) NY84A: BASF Japan, thermoplastic polyurethane elastomer Elastollan (registered trademark) NY88A: BASF Japan, thermoplastic polyurethane elastomer Elastollan (registered trademark) NY95A: BASF Japan, thermoplastic polyurethane elastomer Tinuvin (registered trademark) 770: BASF Japan, hindered amine light stabilizer Titanium dioxide: Ishihara Sangyo Kaisha, Ltd., A-220
[0120] (4) Preparation of spherical cores The core composition shown in Table 1 was hot-pressed in upper and lower molds having hemispherical cavities to obtain a spherical core. An appropriate amount of barium sulfate was added so that the mass of the resulting golf ball would be 45.3 g.
[0121] (5) Formation of the mid-layer and cover The intermediate layer composition was injection molded onto a spherical core to obtain an intermediate layer-coated sphere. The intermediate layer-coated sphere obtained was placed into a final mold having a large number of dimples on the cavity surface. A half shell was obtained from the cover composition by compression molding. Two half shells were coated onto the intermediate layer-coated sphere placed in the final mold to obtain a golf ball in which the outermost cover had a large number of dimples that were the inverse of the pimples on the cavity surface. The evaluation results of the obtained golf balls are shown in Tables 4 to 6.
[0122] [Table 4]
[0123] [Table 5]
[0124] [Table 6]
[0125] From the results in Tables 4 to 6, a golf ball having a spherical core, one or more intermediate layers positioned outside the spherical core, and a cover positioned outside the intermediate layer, the spherical core being formed from a rubber composition containing a rubber component, a co-crosslinking agent, and a crosslinking initiator, the co-crosslinking agent containing methacrylic acid and / or a metal salt thereof, the central hardness (Shore C hardness) of the spherical core, the hardness (Shore C hardness) at points 2.5 mm, 5 mm, 7.5 mm, 10 mm, 12.5 mm, and 15 mm from the center of the spherical core toward the surface, and the surface hardness (Shore C hardness) of the spherical core are H0, H 2.5 , H5, H 7.5 , H 10 , H 12.5 , H 15 , H S When the above equation is satisfied, it can be seen that the golf ball of the present invention which satisfies the following relationship has a low initial velocity on approach shots, a short rolling distance, is excellent in controllability, and provides a good shot feel on approach shots. H0 <H 2.5 <H5<H 7.5 <H 10 <H 12.5 <H 15 <H S [Industrial Applicability]
[0126] The golf ball of the present invention has a low initial velocity on approach shots, a short rolling distance, and is excellent in controllability. The golf ball of the present invention also provides a good shot feeling on approach shots.
[0127] A preferred embodiment (1) of the present invention is a golf ball having a spherical core, one or more intermediate layers positioned outside the spherical core, and a cover positioned outside the intermediate layer, the spherical core is formed from a rubber composition containing a rubber component, a co-crosslinking agent, and a crosslinking initiator; the co-crosslinking agent comprises methacrylic acid and / or a metal salt thereof; The center hardness (Shore C hardness) of the spherical core, the hardness (Shore C hardness) at points 2.5 mm, 5 mm, 7.5 mm, 10 mm, 12.5 mm, and 15 mm from the center toward the surface of the spherical core, and the surface hardness (Shore C hardness) of the spherical core are respectively designated as H0, H 2.5 , H5, H 7.5 , H 10 , H 12.5 , H 15 , H S The golf ball is characterized in that it satisfies the following relationship: H0 <H 2.5 <H5<H 7.5 <H 10 <H 12.5 <H 15 <H S
[0128] A preferred embodiment (2) of the present invention is 2.5 -H0), (H5-H 2.5 ), (H 7.5 -H5), (H 10 -H 7.5 ), (H 12.5 -H 10 ), (H 15 -H 12.5 ), and (H S -H 15 ) is 5 or less.
[0129] A preferred embodiment (3) of the present invention is S-H0) is 20 or less.
[0130] In a preferred embodiment (4) of the present invention, the surface hardness H S has a Shore C hardness of 80 or less, and the spherical core has a central hardness H0 of 60 or less in Shore C hardness.
[0131] A preferred embodiment (5) of the present invention is the golf ball of any one of the embodiments (1) to (4), in which the material hardness Hm of the intermediate layer is greater than the material hardness Hc of the cover.
[0132] A preferred embodiment (6) of the present invention is the golf ball of any one of the embodiments (1) to (5), wherein the intermediate layer has a material hardness Hm of 50 or greater in Shore D hardness.
[0133] A preferred embodiment (7) of the present invention is the golf ball of any one of embodiments (1) to (6), wherein the cover has a material hardness Hc of 40 or less in Shore D hardness.
[0134] A preferred embodiment (8) of the present invention is the golf ball of any one of the embodiments (1) to (7), in which the rubber component is a mixture of polybutadiene, and butyl rubber and / or isoprene rubber.
[0135] A preferred embodiment (9) of the present invention is the golf ball of any one of the embodiments (1) to (8), in which the intermediate layer contains an ionomer resin as the resin component.
[0136] A preferred embodiment (10) of the present invention is a golf ball according to any one of embodiments (1) to (9), wherein the cover contains polyurethane as the resin component.
Claims
1. A golf ball having a spherical core, one or more intermediate layers positioned outside the spherical core, and a cover positioned outside the intermediate layer, the spherical core is formed from a rubber composition containing a rubber component, a co-crosslinking agent, and a crosslinking initiator, The co-crosslinking agent comprises methacrylic acid and / or a metal salt thereof, The center hardness (Shore C hardness) of the spherical core, the hardness (Shore C hardness) at points 2.5 mm, 5 mm, 7.5 mm, 10 mm, 12.5 mm, and 15 mm from the center toward the surface of the spherical core, and the surface hardness (Shore C hardness) of the spherical core are each H 0 , H 2.5 , H 5 , H 7.5 , H 10 , H 12.5 , H 15 , H S A golf ball characterized in that the following relationship is satisfied: H 0 <H 2.5 <H 5 <H 7.5 <H 10 <H 12.5 <H 15 <H S
2. (H 2.5 -H 0 ), (H 5 -H 2.5 ), (H 7.5 -H 5 ), (H 10 -H 7.5 ), (H 12.5 -H 10 ), (H 15 -H 12.5 ), and (H S -H 15 2. The golf ball according to claim 1, wherein each of the above is 5 or less.
3. (H S -H 0 2. The golf ball according to claim 1, wherein the average particle size is 20 or less.
4. The surface hardness H of the spherical core S is 80 or less in Shore C hardness, and the central hardness H 0 2. The golf ball according to claim 1, wherein the hardness of the ball is 60 or less in Shore C hardness.
5. 2. The golf ball according to claim 1, wherein the intermediate layer has a material hardness Hm greater than a material hardness Hc of the cover.
6. 2. The golf ball according to claim 1, wherein the intermediate layer has a material hardness Hm of 50 or greater in Shore D hardness.
7. 2. The golf ball according to claim 1, wherein the cover has a material hardness Hc of 40 or less in Shore D hardness.
8. 2. The golf ball according to claim 1, wherein the rubber component is a mixture of polybutadiene and butyl rubber and / or isoprene rubber.
9. 2. The golf ball according to claim 1, wherein the intermediate layer contains an ionomer resin as a resin component.
10. 2. The golf ball according to claim 1, wherein the cover contains polyurethane as a resin component.
Citation Information
Patent Citations
Golf ball for exercise field
JP1985092780A
Solid golf ball
JP1998192446A
Practice golf ball
JP2012228447A
Practice golf ball
JP2012228448A
Practice golf ball
JP2012228452A